Removal of Methyl Violet Dye from Aqueous solutions using AFe0.9Cu0.1O3 (A= Nd+3 & Eu+3) (Al-Farooq Journal of Sciences, 2026)
Two samples of nanoparticle oxides with general formula NdFe0.9Cu0.1O3 and EuFe0.9Cu0.1O3 were synthesized and their capabilities in the removal of Methyl Violet dye investigated. Both samples have an orthorhombic perovskite-type structure in space group Pbnm. The replacement of Nd3+ ([Xe] 4f3 , 1.27 Å) by Eu3+ ([Xe] 4f6 , 1.23 Å) has influenced removal capacities with no noticeable change in crystal size of the two oxides. The crystallite size of NdFe0.9Cu0.1O3 and EuFe0.9Cu0.1O3 was determined to be 56.10 and 56.40 nm respectively. The  maximum removal capacity  of  Methyl Violet  was found to be  (5.75 and 0.68 mg/g) using NdFe0.9Cu0.1O3 and EuFe0.9Cu0.1O3 respectively. The batch mode study showed that the removal percentage increased as pH increased using EuFe0.9Cu0.1O3 but contributory decreased using NdFe0.9Cu0.1O3. This could be attributed to differences in the electron configurations of the A site cations. The removal of Methyl Violet using  both two oxides has a negative relationship with temperature an ionic strength but steadily increases as contact time increased.
Keywords: Removal, Methyl Violet , Perovskite oxide, A- site Cation